Efeitos do patrimônio líquido dos fundos de investimento em renda fixa brasileiros em sua performance - Pamela Carolina M. Gomes Gaspar Botrel (2018)
Investment funds are financial intermediaries, which offer several advantages to investors, such as investments diversification, professional management, market access, liquidity, transparency, segregation that avoids conflicts of interest, economies of scale and cost reduction. According to data from ANBIMA (2018), assets under management totaled R$ 4.16 trillion at the end of December 2017. Therefore, it has become necessary to study whether the magnitude of fund assets impacts performance. This work aims to determine, within the Brazilian fixed income fund industry, the effect of total asset return on performance and then verify the existence of a range of assets that could arguably maximizes it. The period of analysis was between January 2005 and December 2017 and included active Brazilian fixed income funds. Methodologically, this work has four stages. The first one consisted of estimating performance. As such, the Style-adjusted Gross Return, Sharpe Index adjusted by Israelsen (2005) and alpha were applied. In the second stage, the lag assets were allocated into groups according to size percentiles, so, as to graphically identify the relationship between the mean asset group and performance. In the third phase, the effect of the investment fund assets on performance was estimated in three regression models with panel data, including as an explanatory variable the logarithm of linear, quadratic and cubic total assets. The result demonstrated that for the performance calculated through the Style-Adjusted Return and Sharpe Index, the funds presented an economy of scale with the increase of the volume under management. On the other hand, when using alpha, it was verified that initially the funds suffered diseconomies of scale, but they start to increase returns of scale after the minimum point had been reached. Finally, for the last step, simulated total asset data was used for the graphic visualization of the estimated models. The findings showed that each model presented a distinct range, thus the impact could not be summarized. The results in this research have demonstrated that the fixed income investment funds have a significant influence over the total assets in terms of their performance. However, this relationship changes according to the metric and the fund class studied. Yin (2016) demonstrated that the performance calculated based on the Style-Adjusted Return generated results with less noisy, which was in accord with this study. For this methodology, the sample with all categories and the study of the individual categories generated an interval in which the total assets logarithm was between 10 and 15. For IS and alpha, the results found were distinct and with low significance, which can be justified by the limitations of these measures, mainly for the alpha, because the factors that impact fixed income funds are not consolidated